The analysis of human capital in the context of local economic development - Knapińska, Magdalena; Siński, Wojciech (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The study of local economies has become a significant part of the theoretical and practical approach to economic research. It is important to define variables used for modeling, so the aim of this paper is to identify human capital as the determinant of local economic development. While studies are often conducted on the basis of research material describing a given unit of territorial self-government, the methodology can be applied more broadly. Aim: The aim of the paper is to define the key elements of human capital, which can be used for modeling economic development in the local context. Local development is influenced by a number of factors, such as physical capital, human capital and natural resources, but in this paper we focus both on the analysis of the variables describing human capital both at the moment of examination and of those which will affect its quality in the future. Results: The research findings reveal that human capital in Ustka was subject to significant changes in the period under study and its quality is determined by the economic development of this commune. What is also important is the fact that the variables describing human capital indicate the improvement in the quality of this capital in this territorial unit. Further research into local development should thus take into consideration this significant aspect of economy.